(untitled) (Research, Society and Development, 2022)
Cervical cancer is the disease most often related to Human Papillomavirus (HPV). Cervical cancer is characterized by a multiplication of cells and can reach nearby and even distant tissues. HPV infection associated with other risk factors, such as a history of other sexually transmitted diseases, smoking and use of oral contraceptives, plays an important role in the progression of squamous intraepithelial lesions to malignancy in Brazilian women. The objective is to report the academic experience in the face of an educational awareness about the importance of carrying out the preventive examination, from an interactive conversation circle in a Municipal Health Unit (UMS), located in Belém in the State of Pará. It is an experience report, with a qualitative approach, carried out with women who were waiting for the consultation to carry out the preventive examination. As a component of the multidisciplinary team in primary care, health professionals are responsible for promoting educational actions in order to provide knowledge and clarify doubts about the proposed theme. Based on the proposed dynamics, it was noted the importance of information about performing the preventive examination for early detection of cervical cancer.